2023
DOI: 10.1038/s41598-023-30969-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in morphotype composition of pelagic Sargassum influx events is linked to oceanic origin

Abstract: The recent proliferation of pelagic Sargassum spp. in the Tropical Atlantic causes major ecological and socioeconomic impacts to the wider Caribbean when it washes ashore, with regional fisheries and tourism industries particularly affected. The Caribbean influxes have been tracked to a new bloom region known as the North Equatorial Recirculation Region (NERR) encompassing the area between the South Equatorial Current and the North Equatorial Counter Current and extending from Africa to South America. The vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
1
14
1
Order By: Relevance
“…During Caribbean sargassum influxes, S. natans I and VIII, and S. fluitans III have been shown to be the dominant morphotypes, and their relative abundance varied across seasons, years, and regions (31)(32)(33)(34)(35). S. fluitans III was the predominant morphotype on the Mexican Caribbean coast between September 2016 and May 2020 (31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During Caribbean sargassum influxes, S. natans I and VIII, and S. fluitans III have been shown to be the dominant morphotypes, and their relative abundance varied across seasons, years, and regions (31)(32)(33)(34)(35). S. fluitans III was the predominant morphotype on the Mexican Caribbean coast between September 2016 and May 2020 (31).…”
Section: Discussionmentioning
confidence: 98%
“…The EU-Roadmap for the blue economy reported that the seasonal variation in biomass composition is a characteristic of seaweeds that can affect the scalability of production and the logistical processes (24). In the last few years, there have been increasing reports on seasonal variations of the biochemical (25)(26)(27) and elemental (28)(29)(30) composition of sargassum, as well as on seasonal changes in the morphotype abundance (31)(32)(33)(34)(35).…”
Section: Significancementioning
confidence: 99%
“…The choice to consider varying internal nutrient quotas (C:N:P stoichiometry) is motivated by observations suggesting that Sargassum , like other brown algae, is able to store some nutrients in its tissues (Hanisak, 1983; Lapointe, 1995; Lapointe et al., 2021). In situ observations have also revealed that three different morphotypes are involved in the proliferation ( Sargassum fluitans III, Sargassum natans I, and Sargassum natans VIII e.g., Alleyne et al., 2023; Dibner et al., 2022; García‐Sánchez et al., 2020; Schell et al., 2015). The eco‐physiological features are species dependent, and it has been shown that Sargassum fluitans III, which has been the dominant morphotype over the recent years (García‐Sánchez et al., 2020), grows significantly faster than the Sargassum natans morphotypes (Changeux et al., 2023; Corbin & Oxenford, 2023; Magaña‐Gallegos et al., 2023a, 2023b).…”
Section: Materials and Methods: The Forecasting Strategymentioning
confidence: 99%
“…In 2023, it is only now evident that the most dominant sargassum morphotype in peak Caribbean sargassum seasons has been S. fluitans III [48,55,56]. Nevertheless, morphotype composition of sargassum rafts is highly variable across space and time [48,57], and the quality and quantity of commercially important compounds such as mannitol, alginates, fucoidans and fucoxanthin vary among morphotypes [51,56].…”
Section: Technology and Valorisationmentioning
confidence: 99%